Evaluation of the Influence of Lightning Overvoltage Propagation on Wind Turbine and “Mix” Overhead-Cable Lines - Pham, Thanh Chung (Smart Systems and Devices, 2021)
Due to the growing demand for new and renewable energies and a favorable geographical position, Vietnam is constructing many wind farms. Besides the advantages of being environmentally friendly and the primary endless source of materials, wind farms have disadvantages, for example, high-structured wind towers are usually built in high, empty places and the resistivity of large soil is vulnerable to lightning damage. In this research, we investigate the effects of overvoltage due to lightning strikes on the wings of wind turbines and propagation causing overvoltage on the insulation of cable in the control cable and mixed-lines. The paper also considers the overvoltage protection measures propagated into the insulation equipment and cable insulation using EMTP-RV simulation software